A new species of salamander (Bolitoglossa: Plethodontidae) from the Cordillera Oriental of the Colombian Andes - Andrés R. Acosta-Galvis (Papéis Avulsos de Zoologia, 2012)
Eight species of salamanders are recognized to Cordillera Oriental of Colombia. Here we describe a new species of the genus Bolitoglossa, named Bolitoglossa guaneae sp. nov. The highest number of species of this genus is found in the cloud forests located in the western flank of the Cordillera Oriental.